Adherence to 24-hour movement guidelines in children with mental, behavioral, and developmental disorders: Data from the 2016–2020 National Survey of Children's Health - Ning Pan; Li-Zi Lin; George P. Nassis; Xin Wang; Xiao-Xuan Ou; Li Cai; Jin Jing; Qiang Feng; Guang-Hui Dong; Xiu-Hong Li (Journal of Sport and Health Science, 2023)
Background: Adopting a healthy lifestyle during childhood could improve physical and mental health outcomes in adulthood and reduce relevant disease burdens. However, the lifestyles of children with mental, behavioral, and developmental disorders (MBDDs) remains under-described within the literature of public health field. This study aimed to examine adherence to 24-hour movement guidelines among children with MBDDs compared to population norms and whether these differences are affected by demographic characteristics. Methods: Data were from the 2016–2020 National Survey of Children's Health—A national, population-based, cross-sectional study. We used the data of 119,406 children aged 6–17 years, which included 38,571 participants with at least 1 MBDD and 80,835 without. Adherence to the 24-hour movement guidelines was measured using parent-reported physical activity, screen time, and sleep duration. Results: Among children with MBDDs, 20.3%, 37.0%, 60.7%, and 77.3% met the physical activity, screen time, sleep, and at least 1 of the 24-hour movement guidelines. These rates were lower than those in children without MBDDs (22.8%, 46.2%, 66.7%, and 83.4%, respectively; all p < 0.001). Children with MBDDs were less likely to meet these guidelines (odds ratio (OR) = 1.21, 95% confidence interval (95%CI): 1.13–1.30; OR = 1.37, 95%CI: 1.29–1.45; OR = 1.29, 95%CI: 1.21–1.37; OR = 1.45, 95%CI: 1.35–1.56) than children without MBDDs. Children with emotional disorders had the highest odds of not meeting these guidelines (OR = 1.43, 95%CI: 1.29–1.57; OR = 1.48, 95%CI: 1.37–1.60; OR = 1.49, 95%CI: 1.39–1.61; OR = 1.72, 95%CI: 1.57–1.88) in comparison to children with other MBDDs. Among children aged 12–17 years, the difference in proportion of meeting physical activity and screen time guidelines for children with vs. children without MBDD was larger than that among children aged 6–11 years. Furthermore, the above difference of meeting physical activity guidelines in ethnic minority children was smaller than that in white children. Conclusion: Children with MBDDs were less likely to meet individual or combined 24-hour movement guidelines than children without MBDDs. In educational and clinical settings, the primary focus should be on increasing physical activity and limiting screen time in children aged 12–17 years who have MBDDs; and specifically for white children who have MBDDs, increasing physical activity may help.